A KEY TO THE SPECIES OF RHABDOCHONA (FILOCHONA) SAIDOV, 1953, (NEMATODA: RHABDOCHONIDAE) PARASITIZING CYPRINID FISHES - Kalia, Deepak C. (2013)
To facilitate the identification of the species of Rhabdochona (Filochona) Saidov, 1953, parasitizing carp fishes, a bipartite key for 12 species of the subgenus is provided. Alarge number of worms, Rhabdochona (Filochona) hellichi turkestanica (Skrjabin, 1917) Moravec et al. 2010, were recovered from Schizothorax plagiostomus Heckel in river Ravi at Chamba, a district of Himachal Pradesh (India).